Assessing the common occupational health hazards and their health risks among oil and gas workers. (August 2021) - Benson, Chizubem; Dimopoulos, Christos; Argyropoulos, Christos D.; Varianou Mikellidou, Cleo; Boustras, Georgios
Abstract: The workplace's burden remains a significant concern to workers in the oil and gas industry, where workers are continually exposed to various kinds of occupational risks. The study aimed to identify the different health hazards and their sources across the oil and gas industry to determine the risks associated with health hazards. Methods: A qualitative approach was employed to identify the different hazards connected with the operational environment. A total of 1000 questionnaires were distributed randomly across the various departments in the Nigerian oil and gas industry, and 327 returned to the research team. Analysis of data was carried out using the SPSS. Results: The result shows that ergonomic hazards were found to be most predominant among the hazards assessed in the industry. Ergonomic hazards are 30%, physical hazards 26%, chemical hazards 23%, psychosocial hazards 18%, and biological 3%. Conclusion: Considering the aims of this study, the hazards that exposed workers to ill-health were identified with their sources in the oil and gas operational environment. Some of the health hazards were identified to have short-term health effects on workers, such as headaches, skin burn, eye and skin irritation, and rashes. In contrast, musculoskeletal disorders, respiratory disease, leukaemia, asphyxiates, hypertension, and cardiovascular disease are long-term health effects caused by other hazards. Recommendations: Adequate supervision should be imposed on the workers in their workplace, proper hazards assessment should be conducted in the industry, and compulsory medical testing should be carried out on workers always to know their health status.